The Association of Reproductive and Lifestyle Factors with a Score of Multiple Endogenous Hormones - Shafrir, Amy L. (Springer US, 2014)
INTRODUCTION: We recently reported that high levels of multiple sex and growth hormones were associated with increased postmenopausal breast cancer risk. Limited research has explored the relationship between reproductive, anthropometric, and lifestyle factors and levels of multiple hormones simultaneously. METHODS: This cross-sectional analysis included 738 postmenopausal Nurses’ Health Study participants who were controls in a breast cancer nested case-control study and had measured levels of estrone, estradiol, estrone sulfate, testosterone, androstenedione, dehydroepiandrosterone sulfate, prolactin, and sex hormone binding globulin (SHBG). A score was created by summing the number of hormones a woman had above (below for SHBG) each hormone’s age-adjusted geometric mean. The association between lifestyle, anthropometric, and reproductive exposures and the score was assessed using generalized linear models. RESULTS: The hormone score ranged from 0 to 8 with a mean of 4.0 (standard deviation = 2.2). Body mass index (BMI) and alcohol consumption at blood draw were positively associated with the hormone score: a 5 unit increase in BMI was associated with a 0.79 (95%CI: 0.63, 0.95) unit increase in the score (p < 0.0001) and each 15 g/day increase in alcohol consumption was associated with a 0.41 (95%CI: 0.18, 0.63) unit increase in the score (p = 0.0004). Family history of breast cancer, age at menarche, and physical activity were not associated with the score. CONCLUSIONS: Reproductive breast cancer risk factors were not associated with elevated levels of multiple endogenous hormones, whereas anthropometric and lifestyle factors, particularly BMI and alcohol consumption, tended to be associated with higher levels of multiple hormones.